Pengaruh Citra Merek, Kualitas yang Dirasa dan Promosi Penjualan terhadap Minat Beli Tiket Kereta Api - Fiqri, Fiqri; Fuady, Ikhsan; Yusnita, Titien (JURNAL KOMUNIKATIO, 2024)
The fierce competition in the transport market makes the companies that operate in this land transport have many challenges to face, so Transport company PT. Kereta Api Indonesia (Persero) on land belongs to this country must have a way to be able to compete with several transportation companies that are on both those in the air and those at sea. On the land itself a lot of competitors ranging from buses, railways, travel, and private vehicles. Certainly to win the competition PT. Kereta Api Indonesia (Persero) needs a way such as promotion of revenue, brand image, and accurately assessed quality to be taken in order to compet not only in the sector of land transport but also with air and maritime transport. Researchers use descriptive methods with a quantitative approach where data collection uses questionnaires. The study's sample population is a S1 student who is on the island of Java. Double linear regression and a descriptive statistical test were employed in this study's data analysis. The study's findings demonstrated that only the brand image with intense purchase intent from the analysis results is known that brand image influences the inclination to make purchases, this is known from the value t (54) = 5,386;P<0,05, whereas the promotion of sales has no influence over buying interest, whereas t(54) = -1,267;P>0,05 and the quality perceived does not have an effect on purchase intent, where t(54 = 0,902;P >0,05. This proves that sales promotion does not affect purchasing interest and the perception of quality does not influence purchase intent.